Hydrate risks and prevention solutions for a high pressure gas field offshore in South China Sea. (1st January 2013) - Zhang, Liang; Huang, Anyuan; Wang, Wei; Ren, Shaoran; Jin, Shukai; Fang, Dake
YC13-4 gas field is located in the west of the South China Sea, where the seawater depth is around 90 m, and the average surface temperature is 26.2°C, while the minimum temperature at seabed is 18.9°C. Subsea wellheads are designed for gas production. In this paper, the risks of hydrate formation during drilling, well testing and gas production are analysed under different operation conditions. The results show that most hydrate problems will occur during shutdown and restart operations, and the degree of hydrate occurrence is slight to medium, which poses difficult tasks for choosing safe, reliable and economic methods to mitigate the hydrate problems. Various solutions for hydrate control in different processes are considered, including filling the wellbore with drilling/completion fluids or seawater for pressure control during shutdowns, and injection of methanol into wellbore and subsea pipeline during production. A simple and economic method using down-hole chokes to reduce gas pressure before it enters the hydrate stability zone is introduced, and the placement depth of the down-hole choke is determined.